2013
DOI: 10.1124/mol.113.086553
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Interact with Melanoma Differentiation Associated-7/Interleukin-24 to Kill Primary Human Glioblastoma Cells

Abstract: We presently demonstrate that histone deacetylase inhibitors (HDACIs) enhance toxicity of melanoma differentiation-associated gene-7/interleukin 24 (mda-7/IL-24) in invasive primary human glioblastoma multiforme (GBM) cells. Additionally, a method is described to augment the efficacy of adenoviral delivery of mda-7/IL-24 in these cells. HDACIs synergized with melanoma differentiation-associated (MDA)-7/IL-24 killing GBM cells. Enhanced lethality correlated with increased autophagy that was dependent on the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Antibody reagents, other kinase inhibitors, caspase inhibitors cell culture reagents, and non-commercial recombinant adenoviruses have been previously described. [21][22][23][25][26][27][28] …”
Section: Methodsmentioning
confidence: 99%
“…Antibody reagents, other kinase inhibitors, caspase inhibitors cell culture reagents, and non-commercial recombinant adenoviruses have been previously described. [21][22][23][25][26][27][28] …”
Section: Methodsmentioning
confidence: 99%
“…PERK inhibition blocked ceramide generation, which was critical for Ca 2+ elevation and subsequent ROS formation [ 136 ]. It was also demonstrated that histone deacetylase inhibitors enhance toxicity of IL-24 in invasive primary human GBM cells by synergizing with IL-24 killing effect [ 137 ]. Interestingly, enhanced lethality correlated with increased autophagy that was dependent on the expression of CerS6.…”
Section: Ceramide In Necrotic and Autophagic Death Of Gbm Cellsmentioning
confidence: 96%
“…It has also recently been shown that histone deacetylase inhibitors (HDACIs) increase MDA-7/IL-24 lethality through mechanisms involving ER stress and activation of the extrinsic apoptosis pathway (94). Adenoviral delivery of mda-7/IL-24 to GBM cells and tumors can be enhanced by a serotype 3 tropism modification and by engineering of the virus to conditionally replicate in tumor cells (99). This approach constitutes an attractive adjuvant therapeutic strategy for GBM.…”
Section: Gene Therapeutic Targets For Glioblastomamentioning
confidence: 99%